USING DIGITAL MARKETING TOOLS TO INCREASE THE EFFICIENCY OF THE ENTERPRISE - Dilyora Xashimova Pakhritdinovna; Gulnozaxon Mirziyodova Ayubxon qizi (Scholar Express Journals, 2024)
This article discusses the issues of increasing the efficiency of a trading company using digital marketing, in particular using Internet marketing tools such as search engine optimization, contextual advertising, Google Maps, social media promotion and E-mail marketing, as well as artificial intelligence and web analytics.
Keywords: Search engine optimization; contextual advertising; Google Maps service